Migrant workers in small London hotels: Employment, recruitment and distribution. (July 2016) - Markova, Eugenia; Anna, Paraskevopoulou; Williams, Allan M; Shaw, Gareth
Although migrants dominate employment in many major cities, the reasons for this, and the mechanisms by which they are recruited, are surprisingly under-researched. Focusing on the numerically dominant small hotel sub-sector in a global city, London, the paper first questions whether labour costs or competences are the main drivers of migrant employment, emphasising the difficulties of disentangling the relationships between these. Secondly, it analyses how migrant workers are recruited, and finds less evidence to support the concepts of ethnic queuing and co-ethnic recruitment as opposed to diversified migrant recruitment in the context of the super-diversity of migrant populations in a global city. Finally, it demonstrates that although there are compelling reasons for migrant employment in London's small hotels, and that this is supported by a number of recruitment practices, they are unevenly distributed across establishments, reflecting the complex nature of migrant employment in a highly diverse sub-sector. The research utilises mixed methods, drawing on a survey of 155 hotel managers and 51 in-depth interviews.